The Influence of Transformational Leadership and Organizational Culture on Employee Performance - Jeje Abdul Rojak; Sanaji Sanaji; Andre Dwijanto Witjaksono; Anang Kistyanto (LP. Ma'arif Janggan Magetan, 2024)
Leadership and organizational culture include elements that shape and support individuals in achieving set goals, which in turn affect the overall success of the organization. This study intends to identify the impact of transformational leadership and organizational culture on employee performance. For this study, the sample was 120 staff from three universities and the results were obtained through SPSS (26). The research instrument uses quantitative methods, while data analysis techniques include validity, reliability, classical assumption tests, normality, heteroscedasticity, autocorrelation, multicollinearity, t test and multiple regression. The results showed that with the acceptance of the first hypothesis results, it means that transformational leadership (X1) has an effect on staff performance (Y), indicating that this leadership style has a positive impact on the ability of staff to achieve organizational goals. Acceptance of the second hypothesis shows that organizational culture (X2) significantly affects staff performance (Y) positively. This indicates that the values, norms, and practices contained in the organizational culture have an important role in shaping the performance of the staff.